State Crime : Current Perspectives. - Rothe, Dawn, 1961- (Critical issues in crime and society., 2010)
Current media and political discourse on crime has long ignored crimes committed by States themselves, despite their greater financial and human toll. For two decades, scholars have examined how and why States violate their own laws and international law and explored what can be done to reduce or prevent these injustices. Through essays by leading scholars, State Crime offers a set of cases exemplifying state criminality along with various methods for controlling governmental transgressions. It is an indispensable resource for those who examine the behavior of States and those who study crime.